METHODS OF NORMATIVE MONETARY EVALUATION OF LAND: LEGAL FEATURES - Zhmur, Nataliia; Bokovenko, Vita (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
The purpose of the article is to highlight the legal features of the methodology of normative monetary valuation of land, as well as the difficulties that arise in practice in the process of their use. Research methods: in the course of work the methods of analysis, synthesis, method of comparison, dialectical method, method of interpretation, formal-legal method are used. Results: methods of normative monetary valuation of land are investigated. Methods of conducting monetary valuation of land revealed non-compliance with the basic provisions of the concept of sustainable development. Therefore, it is advisable to introduce the rational and efficient use of land as a scientifically sound use of these plots and other inextricably linked real estate and natural resources by citizens, enterprises, institutions and organizations, which is carried out in compliance with applicable law, based on broad application of the latest technologies, taking into account the interests of present and future generations, to obtain balanced economic, environmental and social effects. Discussion: features of the methodology of monetary valuation of land. The National Standards "General Principles of Property Valuation and Property Rights" have been studied; "Real estate appraisal", their advantages and disadvantages are analyzed. Features of regulatory assessment in foreign countries. The problems of legislative regulation are substantiated, as well as the difficulties that may arise in the practice of applying the methodology of normative monetary valuation of land. The authors conclude that the study of current methods of monetary valuation of land has revealed non-compliance with the basic provisions of the concept of sustainable development. Therefore, it is advisable to introduce the rational and efficient use of land as a scientifically sound use of these plots and other inextricably linked real estate and natural resources by citizens, enterprises, institutions and organizations, which is carried out in compliance with applicable law, based on broad application of the latest technologies, taking into account the interests of present and future generations, to obtain balanced economic, environmental and social effects.